2013
DOI: 10.1111/rec.12015
|View full text |Cite
|
Sign up to set email alerts
|

Restoration Potential of Sedge Meadows in Hand‐Cultivated Soybean Fields in Northeastern China

Abstract: Sedge meadows can be difficult to restore from farmed fields if key structural dominants are missing from propagule banks. In hand-cultivated soybean fields in northeastern China, we asked if tussock-forming Carex and other wetland species were present as seed or asexual propagules. In the Sanjiang Plain, China, we compared the seed banks, vegetative propagules (below-ground) and standing vegetation of natural and restored sedge meadows, and handcultivated soybean fields in drained and flooded conditions. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…(Silvertown et al 1999). Former studies have demonstrated that these six wetland species can coexist in wetlands but may differ in their ability of resource utilization, such as utilization of light, CO 2 and soil nutrients (Lai et al 2012;Wang et al 2013;Wu and Chen 2004;Ye et al 2014). We conclude that hydrological fluctuation can decrease biomass of wetland plant communities but may not alter the diversity-productivity relationship.…”
Section: Discussionmentioning
confidence: 68%
“…(Silvertown et al 1999). Former studies have demonstrated that these six wetland species can coexist in wetlands but may differ in their ability of resource utilization, such as utilization of light, CO 2 and soil nutrients (Lai et al 2012;Wang et al 2013;Wu and Chen 2004;Ye et al 2014). We conclude that hydrological fluctuation can decrease biomass of wetland plant communities but may not alter the diversity-productivity relationship.…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, these types of species generally have long-lived seed banks that could support their re-establishment after flooded conditions return to the wetland (Middleton et al, 1991). Furthermore, our study suggests that aquatic species with robust roots and propagules in the short-term and seed banks in the long-term might be used for the restoration of monsoonal wetlands (Wang et al, 2013).…”
Section: Implications For Managementmentioning
confidence: 89%
“…1) so that concerns have been raised about the drying of these wetlands (Sebastion, 2012). Nevertheless, a counter-trend has developed in recent years in Asia, so that wetland restoration programs have emerged, particularly to create wildlife corridors and recreational parks (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental vectors were examined based on continuous variables including SOC, AN, AP, TK, Na + , Cl - , SO 4 2- , pH, EC, RSC, Alkalinity, SAR and ESP. Data were centered and scaled prior to the analysis [ 5 ], which was carried out using the Vegan Package in R [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence of global environmental changes and human utilization, many of the world’s ecosystems have degraded since the middle of the 20th century, including large proportions of grasslands [ 1 4 ], wetlands and coastal saline marshes [ 5 , 6 ] and forests [ 7 ]. Restoration of these degraded ecosystems is an increasingly relevant focus of current ecological research [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%